Targeted optogenetic stimulation of parasympathetic cholinergic nerve fibers reveals cholinergic-purinergic cotransmission in the bladder detrusor muscle - Mirsaidov, Nodir; Justus Liebig University Giessen (My University, 2018)
Parasympathetic nerve fibers control the contraction of the bladder musculature. Only a third of the contraction induced by their general activation through EFS is inhibited by antagonists of muscarinic ACh receptors. The remaining contraction is predominantly mediated via purinergic receptors. However, it is unclear whether purinergic ligands are released together with ACh from the same nerve fibers, or from a separate fiber population. We have clarified this question in a transgenic animal model with an optogenetic approach. Here, a light-sensitive channel, ChR2, is expressed in cholinergic neurons so that they can be selectively excited by light at a wavelength of 460 nm.A mouse line expressing a ChR2-dtTomato fusion protein under control of the ChAT promotor was generated by crossing the strains B6N.129S6(B6)-Chattm2(cre)Lowl/J and B6;129-Gt(ROSA)26Sortm1(CAG-COP4*E123T*H134R,-tdTomato)Gfng/J. ChR2-dtTomato expression in the urinary bladder and reference organs was characterized by immunofluorescence microscopy. Detrusor contractions were measured in an organ bath in response to EFS and LED (460 nm) stimulation. As a control group, we used a ChAT-eGFP mouse strain that does not express ChR2. Immunofluorescence microscopy revealed expression of the ChR2-dtTomato fusion protein in cholinergic (ChAT- and VAChT-positive), but not other (noradrenergic, peptidergic sensory) nerve fibers in the urinary bladder and other peripheral organs (e.g. airways and duodenum). EFS led to a frequency-dependent contraction in all strains. LED stimulation evoked a contraction of the urinary bladder only in the ChR2-expressing mouse strain so that thermal effects were excluded. Atropine completely inhibited the muscarine-induced contraction of the bladder but reduced the LED-evoked contraction of the detrusor only by 35%. The application of purinergic receptors antagonists, suramin and PPADS, reduced the LED-induced contraction of the detrusor by 60%. Even after combined cholinergic muscarinic and purinergic inhibition, approximately 20% of the LED-induced contraction remained.For the first time, this optogenetic approach proves cholinergic-purinergic cotransmission in the detrusor by releasing at least two transmitters from the same nerve fiber. The remaining contraction after combined blockade of muscarinic cholinergic and purinergic (P2) receptors may result from a minor ectopic expression of ChR2 in the detrusor muscle or another transmitter system, which can be clarified by further investigations using this model.

Parasympathische Nervenfasern steuern die Detrusorkontraktion. Eine vollständige Inhibition der cholinergen Übertragung hemmt die durch generelle Nervenstimulation (elektrische Feldstimulation) induzierte Kontraktion nur zu einem Drittel. Die verbleibende Kontraktion wird vorwiegend über purinerge Rezeptoren vermittelt. Unklar ist jedoch, ob die purinergen Liganden gemeinsam mit ACh aus den gleichen Nervenfasern freigesetzt werden, oder aus einer separaten Faserpopulation. Wir haben diese Frage in einem transgenen Tiermodell mit optogenetischem Ansatz geklärt. Hierbei wird ein lichtsensitiver Kanal, ChR2, in cholinergen Neuronen exprimiert, sodass diese selektiv durch Licht einer Wellenlänge von 460 nm erregt werden können.Eine Mauslinie, die ein ChR2-tdTomato-Fusionsprotein unter der Kontrolle des ChAT-Promotors exprimiert, wurde durch Kreuzung der Stämme B6N.129S6(B6)-Chattm2(cre)Lowl/J und B6;129-Gt(ROSA)26Sortm1(CAG-COP4*E123T*H134R,-tdTomato)Gfng/J generiert. Die ChR2-dtTomato Expression wurde in der Harnblase und Referenzorganen durch (Immun)fluoreszenzmikroskopie charakterisiert. Detrusor-Kontraktionen wurden im Organbad nach EFS und Lichtstimulation (LED, 460 nm) gemessen. Als Kontrollgruppe wurde ein ChAT-eGFP-Mausstamm ohne ChR2-Expression verwendet. Die Immunfluoreszenz zeigte eine Expression des ChR2-tdTomato-Fusionsproteins in cholinergen (ChAT- und VAChT-positiv), aber nicht anderen (nordrenergen, peptiderg-sensorischen) Nervenfasern in der Harnblase und anderen peripheren Organen (z.B. Atemwege, Duodenum). Eine elektrische Stimulation aller Fasern führte in beiden Mausstämmen zu einer frequenzabhängigen Kontraktion. Die optische Stimulation durch LED-Lichtfaser kontrahierte ausschließlich ChR2-exprimierende Blasen, so dass thermische Effekte ausgeschlossen werden konnten. Atropin inhibierte vollständig die durch Muskarinzugabe induzierte Kontraktion, führte aber nur zu einer Verminderung der LED-evozierten Kontraktion um 35 %. Die gemeinsame Zugabe von Antagonisten purinerger Rezeptoren (Suramin und PPADS) reduzierte den LED-Effekt um 60 %. Auch nach gleichzeitiger Gabe von Atropin, Suramin und PPADS verblieb ein Resteffekt von 20 %.Dieser optogenetische Ansatz weist erstmals eine cholinerg-purinerge Kotransmission im Detrusor durch Freisetzung zumindest zweier kleinmolekularer Transmitter aus der gleichen Nervenfaser nach. Die verbleibende Kontraktion nach Blockade cholinerger muskarinischer und purinerger (P2) Rezeptoren kann durch eine geringe ektope Expression des ChR2 in einzelnen glatten Muskelfasern oder auch durch ein weiteres Transmittersystem hervorgerufen werden, was durch weiterführende Untersuchungen in diesem Modell geklärt werden kann.
Keywords: optogenetic; detrusor; channel rhodopsin; ddc:610